Effect of Glass Ceiling on Women’s Career Development in Banks Operating in Pokhara Metropolitan City - Lama, Bijay (Journal of Nepalese Business Studies, 2019)
Although the number of working Nepali women is in the increasing trend, there is lack of data indicating exact number of Nepali women involved in managerial jobs. The general purpose of the study is to find out the effect of glass ceiling on women career development in banks operating in Pokhara Metropolitan City. The dependent variable is career progression refers, employee interested in advancing or achieving their career. Hypotheses indicate that there are significant impact of personal, organizational and societal barrier on women career development. The population which has been selected for the study was female employees working at lower, middle and higher levels of selected commercial banks, development banks and finance companies. The female employees have been selected for this survey and sample size of this study was 99. This research study relied upon the survey method for collection of data. The Cronbach’s alpha test was conducted for reliability which resulted 0.727 that define data are closest to reality. The study found that among the glass ceiling’s factors most influencing factor is societal barrier. Hence, female employee must have to work in order to avoid the societal barriers. Difficulty in maintaining family and job responsibilities; and lack of family support results women employees not to accept higher post. It is suggested to the financial institutions to conduct activities that focus on maintaining balance between work and family life.